MECHANICAL MODEL FOR HUMAN BALANCING ON ROLLING BALANCE BOARD - Csenge A. Molnar; Ambrus Zelei; Tamas Insperger (Acta Polytechnica CTU Proceedings, 2018)
A two-degree-of-freedom mechanical model was developed to analyze human balancing on rolling balance board in the frontal plane. The human nervous system is modeled as a proportionalderivative controller with constant feedback delay. The radius R of the wheels and the board distance h measured from the center of the wheel are adjustable parameters. Simulation results using the mechanical model were compared with real balancing trials recorded by an OptiTrack motion capture system. The goal of the paper is to investigate whether the two-degree-of-freedom model is accurate enough to model the balancing task and to introduce a stabilometry parameter in order to characterize balancing skill in case of different set of R and h. The conclusion is that the angle of the upper body and the angle of the head also play an important role in the balancing process therefore a three- or four-degree-of-freedom model is more appropriate.